Malabar Ulema in the Shafiite Cosmopolis: Fitna, Piety and Resistance in the Age of Fasad - P.K. Yasser Arafath (The Medieval History Journal, 2018)
This article is an attempt to investigate the connections between Muslim ulema of Malabar and the general Muslim population in the Indian Ocean region. The ulema were part of an ever-evolving transnational knowledge network of this region in which various kinds of scholars and texts were in continuous motion. In the sixteenth century, in the wake of the expansion of Portuguese imperial ambitions, the ulema conceived of the importance of building Islamic communities of multiple resistances around Shafiite texts and discourses. It looks at the complex scribal and hortatory engagements of the Malabar ulema and examines three major forms of resistance— pietistic, jurisprudential and physical—that they produced in the larger Indian Ocean region. Therefore, this article moves beyond the existing historiography that focuses on jihad (armed resistance) narratives, and demonstrates alternative ways of reading the period—which included the multiple ways in which the ulema constructed a consistent consciousness of resistance against the Portuguese. Arguments in the article are located within the concepts of fasad (social and political disorder) and fitna (collapse of internal cohesion)—two major Islamic social and political categories. They, I show, attained very specific scribal and theological significance in the Indian Ocean textual network in the sixteenth century, and also acquired particular kinds of textual idioms.